Slow magnetization dynamics in Co(ii)/Co(iii) triethanolamine/pivalate complexes - Sarto, Carolina (2018)
We report the synthesis, structural characterization and a combined computational and experimental study of the magnetic properties of two pivalate cobalt complexes, a mononuclear Co(ii) one and a tetranuclear Co(ii)3Co(iii) mixed valence polynuclear one. The latter shows SMM behaviour revealed under an applied DC field with a thermal barrier of ca. 30 cm-1 competing with direct and Raman relaxation processes. The Orbach thermal barrier can be understood from the doublets energy ladder arising from the anisotropic exchange interaction among ground Seff = 1/2 of each Co(ii) sites. The strong local zero-field splitting of the S = 3/2 Co(ii) states affords these well isolated ground Kramers doublets. DC and AC magnetic susceptibility measurements as well as HF-EPR spectra support this interpretation. CASSCF quantum chemical computations have been also performed in order to aid the overall comprehension of the magnetic behaviour in the reported complexes.